Anticancer Properties of the Antipsychotic Drug Chlorpromazine and Its Synergism With Temozolomide in Restraining Human Glioblastoma Proliferation In Vitro - Matteoni, Silvia; Matarrese, Paola; Ascione, Barbara; Buccarelli, Mariachiara; Ricci-Vitiani, Lucia; Pallini, Roberto; Villani, Veronica; Pace, Andrea; Paggi, Marco G.; Abbruzzese, Claudia (Frontiers in Oncology, 2021)
The extremely poor prognosis of patients affected by glioblastoma (GBM, grade IV glioma) prompts the search for new and more effective therapies. In this regard, drug repurposing or repositioning can represent a safe, swift and inexpensive way to bring novel pharmacological approaches from bench to bedside. Chlorpromazine, a medication used since six decades for the therapy of psychiatric disorders, shows in vitro several features that make it eligible for repositioning in cancer therapy. Using six GBM cell lines, three of which growing as patient-derived neurospheres and displaying stem-like properties, we found that chlorpromazine was able to inhibit viability in an apoptosis-independent way, induce hyperdiploidy, reduce cloning efficiency as well as neurosphere formation and downregulate the expression of stemness genes in all these cell lines. Notably, chlorpromazine synergized with temozolomide, the first-line therapeutic in GBM patients, in hindering GBM cell viability, and both drugs strongly cooperated in reducing cloning efficiency and inducing cell death in vitro for all the GBM cell lines assayed. These results prompted us to start a Phase II clinical trial on GBM patients (EudraCT # 2019-001988-75; ClinicalTrials.gov Identifier: NCT04224441) by adding chlorpromazine to temozolomide in the adjuvant phase of the standard first-line therapeutic protocol.